Method of Optimization in Financial Forecasting - M.U., Mukhammadjonov (Journal of Sustainability in Integrated Policy and Practice, 2025)
Financial forecasting is a critical element of enterprise management, enabling organizations to predict revenues, manage expenses, and maintain financial stability in both short- and long-term horizons. The accuracy of forecasts depends not only on available data but also on the selected forecasting methods and optimization strategies. This article explores traditional and modern approaches to financial planning and forecasting, emphasizing optimization methods such as scenario analysis, discounted cash flow techniques, and economic-mathematical modelling. The review highlights the growing role of machine learning, big data analytics, and hybrid forecasting models as powerful tools for enhancing prediction accuracy.